6 - Transition from shacks to formal human settlements – Social cohesion in Mt Moriah in the metropolitan area of Durban, South Africa. - Sultan Khan, (African Sociological Review, 2019)
The transition from shack to formal human settlements can be very traumatic. It means abandoning old habits, lifestyles, relationships and forming new ones. The extent to which those that have been relocated to new settlements adjust and adapt to new forms of community life would be determined by the nature and extent of social cohesion prevalent in that community. A lack of social cohesion within resettled communities makes it prone to various forms of social disorganisation which manifests itself in a variety of social problems. The study was informed by 150 interviews with respondents selected in the different precincts of the study locality using a non-probability sampling technique. In the case of Mt Moriah, a formal human settlement it was more than a decade that residents from a number of shack settlements in the city have been resettled in this locality. It appears from the study that overtime the residents of Mt Moriah have settled down to community and family life and enjoy a strong sense of social cohesion despite many challenges surrounding service delivery and the emergence of social problems. This study highlights that a significant number of members of the community have a sense of belonging in the locality and are aspiring towards bettering their quality of life.